Evaluation of Mucor indicus and Saccharomyces cerevisiae capability to ferment hydrolysates of rape straw and Miscanthus giganteus as affected by the pretreatment method. (July 2016) - Lewandowska, Małgorzata; Szymańska, Karolina; Kordala, Natalia; Dąbrowska, Aneta; Bednarski, Włodzimierz; Juszczuk, Andrzej
Highlights: The comparison of two pretreatment methods of rape straw and M. giganteus . The acid treatment results in a significant removal of hemicellulose from the solid. The highest reducing sugars concentration was found following alkali pretreatment. The used microorganisms revealed a favorable capability for the ethanol fermentation. Abstract: Rape straw and Miscanthus giganteus was pretreated chemically with oxalic acid or sodium hydroxide. The pretreated substrates were hydrolyzed with enzymatic preparations of cellulase, xylanase and cellobiase. The highest concentration of reducing sugars was achieved after hydrolysis of M. giganteus pretreated with NaOH (51.53 g dm −3 ). In turn, the highest yield of enzymatic hydrolysis determined based on polysaccharides content in the pretreated substrates was obtained in the experiments with M. giganteus and oxalic acid (99.3%). Rape straw and M. giganteus hydrolysates were fermented using yeast Saccharomyces cerevisiae 7, NRRL 978 or filamentous fungus Mucor rouxii ( Mucor indicus ) DSM 1191. The highest ethanol concentration was determined after fermentation of M. giganteus hydrolysate pretreated with NaOH using S. cerevisiae (1.92% v/v). Considering cellulose content in the pretreated solid, the highest degree of its conversion to ethanol (86.2%) was achieved after fermentation of the hydrolysate of acid-treated M. giganteus using S. cerevisiae .